Factors contributing to the variation in antibiotic prescribing among primary health care physicians: a systematic review - Kasse, Gashaw Enbiyale; Humphries, Judy; Cosh, Suzanne M.; Islam, Md Shahidul (BMC family practice, 2024)
Background Antibiotic resistance is growing globally. The practice of health professionals when prescribing antibiotics in primary health care settings significantly impacts antibiotic resistance. Antibiotic prescription is a complex process influenced by various internal and external factors. This systematic review aims to summarize the available evidence regarding factors contributing to the variation in antibiotic prescribing among physicians in primary healthcare settings. Methods This systematic review was conducted based on PRISMA guidelines. We included qualitative, quantitative and mixed methods studies that examined factors influencing prescription practice and variability among primary healthcare physicians. We excluded editorials, opinions, systematic reviews and studies published in languages other than English. We searched studies from electronic databases: PubMed, ProQuest Health and Medicine, Web Science, and Scopus. The quality of the included studies was appraised using the Mixed Methods Appraisal Tool (Version 2018). Narrative synthesis was employed to synthesize the result and incorporate quantitative studies. Results Of the 1816 identified studies, 49 studies spanning 2000–2023 were eligible for review. The factors influencing antibiotic prescription practice and variability were grouped into physician-related, patient-related, and healthcare system-related factors. Clinical guidelines, previous patient experience, physician experience, colleagues’ prescribing practice, pharmaceutical pressure, time pressure, and financial considerations were found to be influencing factors of antibiotic prescribing practice. In addition, individual practice patterns, practice volume, and relationship with patients were also other factors for the variability of antibiotic prescription, especially for intra-physician prescription variability. Conclusion Antibiotic prescription practice in primary health care is a complex practice, influenced by a combination of different factors and this may account for the variation. To address the factors that influence the variability of antibiotic prescription (intra- and inter-physician), interventions should aim to reduce diagnostic uncertainty and provide continuous medical education and training to promote patient-centred care.